Simulation‐Optimization Approach for Siting Injection Wells in Urban Area with Complex Hydrogeology - Mok, Chin Man; Carrera, Barbara; Hort, Hiroko; Santi, Lauren; Daus, Anthony; Panday, Sorab; Jones, David; Partington, Brian; Ferguson, Everett (Ground water, 2024)
Managed aquifer recharge has become a standard water resources management practice to promote the development of locally sustainable water supplies and combat water scarcity. However, installation of injection wells for replenishment purposes in urban areas with complex hydrogeology faces many challenges, such as limited land availability, potential impacts on municipal production wells and known subsurface contamination plumes, and complex spatially variable hydraulic connections between aquifer units. To assess the feasibility and cost‐effectiveness of injecting advanced treated water (ATW) into a complex urban aquifer system, a Simulation‐Optimization (SO) model was developed to automate a systematic search for the most cost‐effective locations to install new wells for injecting various quantities of ATW, if feasible. The generalized workflow presented here uses an existing MODFLOW groundwater model—along with advanced optimization routines that are publicly available—to flexibly accommodate a multiobjective function, complex constraints, and specific project requirements. The model successfully placed wells for injection of 1 to 4 MGD of ATW in aquifers underlying the study area. The injection well placement was primarily constrained by avoiding excessive impact on environmental sites with underlying groundwater plumes. The largest costs were for well installation and piping to the wells from the existing ATW pipes. This workflow is readily adaptable to other sites with different complexities, decision variables, or constraints. Simulation‐Optimization of Advanced Treated Water Injection